Ask Your Question
0

Solve for variable but variable is still in answer

asked 2014-08-28 12:49:41 -0600

wzawzdb gravatar image

updated 2014-08-29 08:48:16 -0600

I try to solve for variable P3. Sage gives me an answer for P3 but it still contains P3 on the right hand side (see last equation after the solve in the beginning of sqrt?

sage: A1, A2, A3, P1, P2, P3, u1, u2, u3, r1, r2, r3, g, C, M1, M2, M3 = var('A1 A2 A3 P1 P2 P3 u1 u2 u3 r1 r2 r3 g C M1 M2 M3')
sage: eq1=A3*(P1-P3)==A3*r3*u3^2-(A2*r2*u2^2+A1*r1*u1^2)
sage: eq2=A3*u3*r3==A2*u2*r2+A1*r1*u1
sage: eq5a=solve([eq2],r3)
sage: eq5b=u3^2+2*g/(g-1)*(P3/(eq5a[0].rhs()))-2*C==0
sage: eq6=solve([eq5b],u3)
sage: eq7a=eq1/A3
sage: eq7b=eq7a.subs(-A3*r3*u3^2 == -(A2*u2*r2+A1*r1*u1)*u3)
sage: eq7b
P1 - P3 == -(A1*r1*u1^2 + A2*r2*u2^2 + (A3*P3*g + sqrt(A3^2*P3^2*g^2 + 2*((g^2 - 2*g + 1)*A1^2*r1^2*u1^2 + 2*(g^2 - 2*g + 1)*A1*A2*r1*r2*u1*u2 + (g^2 - 2*g + 1)*A2^2*r2^2*u2^2)*C))*(A1*r1*u1 + A2*r2*u2)/(A1*(g - 1)*r1*u1 + A2*(g - 1)*r2*u2))/A3

sage: eq7c=eq7b.subs(u3==eq6[0].rhs()) 
sage: eq7=solve([eq7c],P3)
sage: eq7
[P3 == (A1*r1*u1^2 + A2*r2*u2^2 + A3*P1 - (A1*r1*u1^2 + A2*r2*u2^2 + A3*P1)*g - sqrt(A3^2*P3^2*g^2 + 2*((g^2 - 2*g + 1)*A1^2*r1^2*u1^2 + 2*(g^2 - 2*g + 1)*A1*A2*r1*r2*u1*u2 + (g^2 - 2*g + 1)*A2^2*r2^2*u2^2)*C))/A3]
edit retag flag offensive close merge delete

Comments

It looks like it sees P3 and P3 as different variables?

wzawzdb gravatar imagewzawzdb ( 2014-08-28 15:39:48 -0600 )edit

Trying to recreate this gave me an error because eq2 was not defined.

rws gravatar imagerws ( 2014-08-29 00:47:53 -0600 )edit

I forgot to copy that line or something, sorry about that

wzawzdb gravatar imagewzawzdb ( 2014-08-29 08:48:42 -0600 )edit

1 answer

Sort by ยป oldest newest most voted
1

answered 2014-08-29 12:06:16 -0600

tmonteil gravatar image

updated 2014-08-31 16:50:05 -0600

First, you should notice that eq6 is a list of two solutions for u3:

sage: len(eq6)
2
sage: eq6
[u3 == -(A3*P3*g + sqrt(A3^2*P3^2*g^2 + 2*((g^2 - 2*g + 1)*A1^2*r1^2*u1^2 + 2*(g^2 - 2*g + 1)*A1*A2*r1*r2*u1*u2 + (g^2 - 2*g + 1)*A2^2*r2^2*u2^2)*C))/(A1*(g - 1)*r1*u1 + A2*(g - 1)*r2*u2), u3 == -(A3*P3*g - sqrt(A3^2*P3^2*g^2 + 2*((g^2 - 2*g + 1)*A1^2*r1^2*u1^2 + 2*(g^2 - 2*g + 1)*A1*A2*r1*r2*u1*u2 + (g^2 - 2*g + 1)*A2^2*r2^2*u2^2)*C))/(A1*(g - 1)*r1*u1 + A2*(g - 1)*r2*u2)]

You can choose the first or the second as follows:

sage: eq6[0]
u3 == -(A3*P3*g + sqrt(A3^2*P3^2*g^2 + 2*((g^2 - 2*g + 1)*A1^2*r1^2*u1^2 + 2*(g^2 - 2*g + 1)*A1*A2*r1*r2*u1*u2 + (g^2 - 2*g + 1)*A2^2*r2^2*u2^2)*C))/(A1*(g - 1)*r1*u1 + A2*(g - 1)*r2*u2)
sage: eq6[1]
u3 == -(A3*P3*g - sqrt(A3^2*P3^2*g^2 + 2*((g^2 - 2*g + 1)*A1^2*r1^2*u1^2 + 2*(g^2 - 2*g + 1)*A1*A2*r1*r2*u1*u2 + (g^2 - 2*g + 1)*A2^2*r2^2*u2^2)*C))/(A1*(g - 1)*r1*u1 + A2*(g - 1)*r2*u2)
sage: eq6[0] == eq6[1]
False

Second, you found the limitation of the solve function, which is not very powerful, so it is sometimes not able to find a solution of the form P3 = .... Youe equation involves squares roots and solve does not handle such equations very well. A simpler example is:

sage: eq = x == sqrt(x)
sage: eq.solve(x)
[x == sqrt(x)]

EDIT It seems that sympy is better than Maxima in solving this, so you can do:

sage: import sympy
sage: sympy.solve(eq7c.rhs()-eq7c.lhs(), P3)
[(A3*(A1*r1*u1**2 + A2*r2*u2**2 + A3*P1) - sqrt(A3**2*(-2*A1**2*C*g**2*r1**2*u1**2 + 2*A1**2*C*r1**2*u1**2 + A1**2*g**2*r1**2*u1**4 - 4*A1*A2*C*g**2*r1*r2*u1*u2 + 4*A1*A2*C*r1*r2*u1*u2 + 2*A1*A2*g**2*r1*r2*u1**2*u2**2 + 2*A1*A3*P1*g**2*r1*u1**2 - 2*A2**2*C*g**2*r2**2*u2**2 + 2*A2**2*C*r2**2*u2**2 + A2**2*g**2*r2**2*u2**4 + 2*A2*A3*P1*g**2*r2*u2**2 + A3**2*P1**2*g**2)))/(A3**2*(g + 1)),
 (A3*(A1*r1*u1**2 + A2*r2*u2**2 + A3*P1) + sqrt(A3**2*(-2*A1**2*C*g**2*r1**2 ...
(more)
edit flag offensive delete link more

Comments

And there are no other options to solve this? I know there are two solutions (quadratic rule) but I take only one with the eq6[0].rhs() right?

wzawzdb gravatar imagewzawzdb ( 2014-08-29 12:21:31 -0600 )edit

yes, eq6 is a Python list that contains all solutions. There are two of them, to get the second one, you just have to look at eq6[1].rhs()

tmonteil gravatar imagetmonteil ( 2014-08-29 17:23:13 -0600 )edit

Why do you subtract eq7c rhs from lhs **=^

wzawzdb gravatar imagewzawzdb ( 2014-09-02 10:18:30 -0600 )edit

@wzawzdb, from the Sympy solvers documentation Use solve() to solve algebraic equations. We suppose all equations are equaled to 0, so solving x**2 == 1 translates into the following code: Run code block in SymPy Live

>>> from sympy.solvers import solve
>>> from sympy import Symbol
>>> x = Symbol('x')
>>> solve(x**2 - 1, x)
[-1, 1]
JesterEE gravatar imageJesterEE ( 2015-02-25 15:52:22 -0600 )edit

Your Answer

Please start posting anonymously - your entry will be published after you log in or create a new account.

Add Answer

Question Tools

1 follower

Stats

Asked: 2014-08-28 12:49:41 -0600

Seen: 186 times

Last updated: Aug 31 '14